Does a big bazooka matter? Central bank balance-sheet policies and exchange rates - Luca Dedola; Georgios Georgiadis; Johannes Gräb; Arnaud Mehl (European Central Bank (ECB), 2018)
We estimate the effects of quantitative easing (QE) measures by the ECB and the Federal Reserve on the US dollar-euro exchange rate at frequencies and horizons relevant for policymakers. To do so, we derive a theoretically-consistent local projection regression equation from the standard asset pricing formulation of exchange rate determination. We then proxy unobserved QE shocks by future changes in the relative size of central banks' balance sheets, which we instrument with QE announcements in two-stage least squares regressions in order to account for their endogeneity. We find that QE measures have large and persistent effects on the exchange rate. For example, our estimates imply that the ECB's APP program which raised the ECB's balance sheet relative to that of the Federal Reserve by 35 percentage points between September 2014 and the end of 2016 depreciated the euro vis-à-vis the US dollar by a 12%. Regarding transmission channels, we find that a relative QE shock that expands the ECB's balance sheet relative to that of the Federal Reserve depreciates the US dollar-euro exchange rate by reducing euro-dollar short-term money market rate differentials, by widening the cross-currency basis and by eliciting adjustments in currency risk premia. Changes in the expectations about the future monetary policy stance, reflecting the "signalling" channel of QE, also contribute to the exchange rate response to QE shocks.
Keywords: E5; F3; 330; Quantitative easing; interest rate parity condition; CIP deviations